Findings of a videofluoroscopic swallowing study in patients with dysphagia - Cui, Qingjia; Wei, Bing; He, Yuan; Zhang, Qian; Jia, Weiwei; Wang, Haiying; Xi, Jianing; Dai, Xin (Frontiers in Neurology, 2023)
Objective Swallowing examination is crucial in patients with dysphagia. We aimed to compare qualitative and quantitative videofluoroscopic swallowing study (VFSS) results to provide reference for standardizing quantitative parameters. Materials and methods In total, 117 patients with dysphagia were included, 38 with Parkinson’s disease and 39 and 40 in convalescence following cerebral hemorrhage and infarction. VFSS was both qualitatively and quantitatively analyzed. Results A significant difference of Oral transit time was found between the oral motor function grades (p < 0.001), also was swallowing reaction times found between swallowing reaction duration grades (p < 0.001), and soft palate lift duration between the soft palate lift grades (p < 0.001). Superior hyoid bone movement (p < 0.001), anterior hyoid bone movement (p < 0.001), hyoid pause time (p < 0.001), and hyoid movement duration (p = 0.032) had significant differences between the hyoid laryngeal complex movement grades, as did the pharyngeal cavity transit time among the cricopharyngeal muscle opening duration grades (p < 0.001). The laryngeal vestibule closure duration differed among the glottic closure grades (p < 0.001). No statistically significant difference in upper esophageal sphincter opening diameter (p = 0.682) or duration (p = 0.682) among the cyclopharyngeal muscle opening duration grades. The pharyngeal area at rest did not significantly differ among the different vallecular residue (p = 0.202) and pyriform sinus residue (p = 0.116) grades. Conclusion Several quantitative parameters can reflect the swallowing assessment process well. Further optimization of quantitative parameters is recommended.